Interval Walking Training for Functional Optimization and Health in The Elderly: A Narrative Review - Ishad, Muhammad Raihan; Rahman, Farid (Universitas Muhammadiyah Surakarta, 2025)
Introduction: The global rise in the older adult population presents challenges in maintaining their functional capacity and health. Aging is associated with declines in physical function, cardiovascular fitness, and metabolism, affecting quality of life. Interval Walking Training offers an adaptive, affordable, and safe exercise option to address these issues.Aim of the Study: This review aims to identify the benefits of Interval Walking Training in optimizing physical function and health in older adults and evaluate protocol variations and their effects.Methods: This narrative review includes seven studies published in the last ten years (2015–2025) and evaluates the effects of Interval Walking Training on various aspects of elderly health. Literature sources were obtained from PubMed, Cochrane, and Google Scholar using the keywords